DIGITALISASI LAYANAN SEWA STUDIO UNTUK UMKM KREATIF: PELATIHAN PENGELOLAAN WEBSITE RESERVASI ONLINE BERBASIS WEB - Koko Setianto; Taufiqurrohman; Dzakwan Avie Rahmanie; Rangga Riharja; Azwa Kurendra Putra Gamma (PEMTEKDIKMAS (PENGABDIAN EKONOMI MULTIDISIPLIN TEKNOLOGI PENDIDIKAN UNTUK MASYARAKAT), 2024)
Studio rental services represent growing segment within creative industries, encompassing photography studios, music production spaces, video recording facilities, and art workshops. However, most micro-scale studio operators maintain manual booking systems creating operational inefficiencies, limited market visibility, and customer accessibility barriers. This Community Service Program (PKM) addressed digitalization needs of Kilas Graduation, a multi-purpose creative studio, through development and implementation of StudioReserve, a comprehensive web-based reservation management system. Program involved: (1) business process analysis; (2) web application development using React and Node.js; (3) practical online management training; and (4) digital marketing implementation. StudioReserve features: real-time room availability calendar, seamless online reservation booking, customer database management, payment integration, business analytics dashboard, and automated confirmation notifications. Participants included 1 owner and 4 staff members. Results after 6 weeks demonstrated: booking volume increased 54%, average booking value increased 32%, customer database expanded (+289%), online booking adoption reached 67%, operational efficiency improved 38%, and cancellation rate decreased 45%. Training satisfaction achieved 87% with 93% competency.